The Implementation of Contextual And Learning (CTL) Model in Critical Thinking Ability on Primary Students' Learning Outcomes - Tobing, Minar Trisnawati (Jurnal Basicedu, 2022)
This study aims to determine the effect of contextual learning and learning (CTL) models in critical thinking leadership on student learning outcomes. the results of data analysis and discussion, it can be concluded that there is an effect of applying a contextual approach to the learning outcomes of Civics on Human Rights in fourth grade students of SD Negeri. By using the inferential analysis technique to test the research hypothesis, in this case the Independent Sample T-test formula is used in the SPSS program. Before testing the hypothesis, the normality test and homogeneity test were first carried out. From the results of the analysis obtained data are normally distributed and homogeneous. Because the data that has been analyzed is normally distributed and homogeneous, it is continued with the T- test using the Independent Sample T- test formula with SPSS. The results of the analysis show that the significance of 0.033 is smaller than = 0.05. Thus H0 is rejected and H1 is accepted